Administration System Analysis at Warehouse PT. Roots of Independent Blessing - Intan Puspita Ayudita Putri Widjanarko; Christian Wiradendi Wolor; Marsofiyati (Formosa Journal of Applied Sciences, 2023)
This research aims to analyze the administration system at the PT Akar Berkat Mandiri Warehouse which occurs because the system is still manual, often making it slower and more time consuming than using an automated system, thus hampering work productivity. This research uses a qualitative descriptive approach method with Non-Probability Sampling, namely by describing and analyzing the problems found. The research results show that there is a problem with the management system of PT Akar Berkat Mandiri, namely that some documents are best because the management of the system is still manual, which makes the data input process take longer and the data input is still messy.